PENERAPAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR DALAM PEMBELAJARAN SENI BUDAYA - Nursakinah, Tsani; Syarif Hidayat, Ujang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of using audiovisual media in improving learning outcomes of elementary school students in Cultural Arts subjects. This research uses a literature review method sourced from various relevant national scientific journals between 2019 and 2025. Data was collected through searching articles using certain keywords such as